Development of a Software Tool to Support System Lifecycle Management - Robin, V.; Brunel, S.; Zolghadri, M.; Girard, P. (Cranfield University Press, 2009)
In the extended enterprise context, many stakeholders act on the product during all its lifecycle. They influence the product development and managers have to be able to control all the activities and their interactions that are generating the different processes. They have also to manage each actor involved in the project during the product lifecycle. In this paper, propose an approach to identify, define and manage factors influencing product development. It is the System Lifecycle Management. PEGASE, a prototype of software to control design project, follow-up the system evolution and support decision-making, is also presented.
Organised by: Cranfield University
Keywords: System Lifecycle Management; Strategic Design Process Management; Computer-Aided Engineering